Can we remove tattoos with non‐thermal atmospheric plasma?. Issue 4 (23rd February 2022) - Tampieri, Francesco; Araguz, Ariadna G.; Canal, Cristina
Abstract: Current methods for tattoo removal are long, costly and have drawbacks such as scarring among others. Looking for alternatives, here we assess the feasibility of non‐thermal plasma (NTP) as a standalone method for the removal of tattoos. We report the results of atmospheric pressure plasma jet treatment of real tattoo inks suspensions in water and in gelatin (liquid or as a solid film), selected as a model of skin. Analysis of the residual color and the temperature effect in all the samples after plasma treatment reveals significant differences between water and the skin model. Kinetic considerations and the extension of our results to more realistic scenarios allow us to conclude that NTP cannot compete with the current laser technology in a real application. Abstract : As an alternative for tattoo removal, we evaluate atmospheric pressure plasma jet treatment of tattoo ink suspensions in water or in gelatin, selected as a model of skin. Analysis of the residual color and the temperature effect in all the samples after plasma treatment reveals significant differences between water and the skin model. Kinetic considerations and the extension of our results to more realistic scenarios allow us to conclude that non‐thermal plasma cannot compete with the current laser technology in view of a real application.